The use of LRS in the management of severe open fracture and infection of femur - Mohd Yusof, Nazri (2014)
Internal fixation of femur is the mainstay in the treatment of open and close femoral fracture. This is due to the good soft tissue envelope in the thigh. However, in the presence of severe soft tissue injury or infection, external fixator provides a safe and reliable treatment option. The conventional external fixation system is not stiff enough to overcome the strong muscle pull in the thigh. The circular external fixation disturb patients daily activity and bulky. The monorail external fixation system (Limb Reconstruction Sytem(LRS) ) provides a more stable fixation without disturbing patients daily activities. The aim of this study is to report the outcome of treating infection following internal fixation of femur using monorail external fixation Eleven patients 10 males and 1 females with the mean age of 29 (range 14 to 56 years old). Eight patients with infection following plate osteosynhtesis, one following interlocking nail of femur, one pathological fracture from hematogenous osteomyelitis,and one open grade IIIC of femur were included in the study. Hydroxyapetite (HA) coated screws were used to minimised loosening of the screws. Acute shortening was done in 10 cases and bone transport in one. Tobramycin pellets were used in 6 cases. Pseudomonas aeruginosa, klebsiella aeruginosa, enterobacter aeregenes, proteus miribilis, bacilus sp, staphylococcus aureus and Methicilline Resistant Staphylococcus aureus was isloated from patients. All achieved controlled of infection and union). In acute shortening, the mean union time is 5.5 months (range 4-7 months) and does not requires bone grafting. The patient with 5 cm bone loss undergone femoral bone transport and require bone grafting at the docking and regenerate site. She achieved union after 30 months of treatment. Stabilisation with a monolateral external fixation provides an effective and convenience methods of fixation for severe open fracture and infection of femur .